PENGARUH RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PABRIK KERTAS PT. TJIWI KIMIA TBK PERIODE 2013 - 2018 - Munandar, Aris (SULTANIST: Jurnal Manajemen dan Keuangan, 2019)
This research was conducted with the aim to determine the effect of Business Risk Towards Capital Structure in Paper Factory Companies PT. Tjiwi Kimia Tbk years 2013 - 2018. The population in this study for 10 (ten) years, starting from the year 2009 -2018. The sampling technique used was purposive sampling and the number of samples obtained for 6 years (2013-2018). The data used are secondary data sourced from the financial statements of PT.Tjiwi Kimia Tbk Paper Factory which are listed on the Indonesia Stock Exchange. Data analysis technique used in this study is simple linear regression, correlation simple, coefficient of determination, and hypothesis testing using t-statistical tests to determine the effect partially between business risk to the structure capital with a significance level of 5%. The results showed that the business risk variable influenced the capital structure. Then the simple correlation value of 0.854 which indicates that the closeness of the relationship between business risk and capital structure at the Paper Factory of PT. Tjiwi Kimia Tbk is very strong. And the value of the coefficient of determination is 0.730, which shows that the contribution of the influence of business risk variables on capital structure at the Paper Factory of PT. Tjiwi Kimia Tbk is 73.0%, and the remaining 27.0% is influenced by other variables not examined in this study.Keywords:Â  Business Risk, Capital Structure.